FEATURES OF ARTICULATION AND DICTION IN THE JUNIOR CHOIR - Makhmudova Mokhimbonu; Khusnitdinova Yulduz Madatovna (Scientific Impulse, 2023)
This article examines the issues of correct use of diction and articulation apparatus in children's choir performance and its development through exercises.